FASHION PRESENTATIONS IN THE SPACE OF WAR DESTRUCTIONS: ETHICS AND AESTHETICS OF PARADOXICALITY - КВАСНИЦЯ, Роксолана Богданівна (Art and Design, 2023)
To conduct the analysis of the presentation of fashion collections in wartime in relation to ethical and aesthetic norms. The research uses theoretical general scientific methods of analysis and synthesis, classification, methods of synchronous and diachronic analysis. The research uses the transcendental method, the comparative method and the heterotopological method has been applied to demonstrate the way visuality and space interact in the presentation of fashion collections. It was determined that the paradox, which occurs when there is the fashion presentation among the ruins during the war, from the point of view of paradoxical intention, can be an effective method of transforming negative perception into positive, influencing the transformation of stressful circumstances into opportunities for personal and interpersonal growth in the destructive conditions of war. According to the results of the analysis of the experience of other countries, it was found that ethical norms should be a priority when creating visual images in the presentation of fashion collections in times of war. Factors influencing the psychological perception of fashion presentations in wartime by the society have been established. Since the presentation of fashion collections is a form of mass communication, socio-psychological mechanisms of influence were analyzed and differentiation was carried out according to the main categories. For the first time, a study was conducted on the definition of ethical and aesthetic standards for the presentation of fashion collections during the wartime. Attention has been focused on the psycho-emotional perception by society of the presentation of fashion during the war. The results of the research can be applied in practice in the process of presenting fashion collections of Ukrainian brands during the war and the post-war period.